Short sleep duration, complaints of vital exhaustion and perceived stress are prevalent among pregnant women with mood and anxiety disorders - Qiu Chunfang; Gelaye Bizu; Fida Neway; Williams Michelle A (BMC, 2012)
Abstract Background Psychiatric disorders have been associated with sleep disorders in men and non-pregnant women, but little is known about sleep complaints and disorders among pregnant women with psychiatric disorders. Methods A cohort of 1,332 women was interviewed during early pregnancy. We ascertained psychiatric diagnosis status and collect information about sleep duration, daytime sleepiness, vital exhaustion and perceived stress. Logistic regression procedures were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results Approximately 5.1% of the cohort (n=68) reported having a physician-diagnosis of mood or anxiety disorder before interview. Compared with women without a psychiatric diagnosis, the multivariable-adjusted OR (95% CI) for short sleep duration in early pregnancy (≤6 hours) were 1.95 (1.03-3.69). The corresponding OR (95%CI) for long sleep duration (≥9 hours) during early pregnancy was 1.13 (0.63-2.03). Women with psychiatric disorders had an increased risk of vital exhaustion (OR=2.41; 95%CI 1.46-4.00) and elevated perceived stress (OR=3.33; 95%CI 1.89-5.88). Observed associations were more pronounced among overweight/obese women. Conclusions Women with a psychiatric disorder were more likely to report short sleep durations, vital exhaustion and elevated perceived stress. Prospective studies are needed to more thoroughly explore factors that mediate the apparent mood/anxiety-sleep comorbidity among pregnant women.